A biologically plausible mechanism for neuronal coding organized by the phase of alpha oscillations. (18th July 2016) - Gips, Bart; van der Eerden, Jan P. J. M.; Jensen, Ole
Abstract: The visual system receives a wealth of sensory information of which only little is relevant for behaviour. We present a mechanism in which alpha oscillations serve to prioritize different components of visual information. By way of simulated neuronal networks, we show that inhibitory modulation in the alpha range (~ 10 Hz) can serve to temporally segment the visual information to prevent information overload. Coupled excitatory and inhibitory neurons generate a gamma rhythm in which information is segmented and sorted according to excitability in each alpha cycle. Further details are coded by distributed neuronal firing patterns within each gamma cycle. The network model produces coupling between alpha phase and gamma (40–100 Hz) amplitude in the simulated local field potential similar to that observed experimentally in human and animal recordings. Abstract : By way of a biologically inspired neural network model, we show that inhibitory modulation in the alpha range (~ 10 Hz) can serve to temporally segment information in visual cortex, to prevent information overload. Coupled excitatory and inhibitory neurons generate a gamma rhythm in which information is segmented and temporally sorted according to excitability in each alpha cycle. The network model produces coupling between alpha phase and gamma (40–100 Hz) amplitude in the simulated local field potential similar to that observed experimentally in human and animal recordings.